A Preserving cultural identity through entrepreneurship: A PRISMA-based systematic review of Indonesian tribal communities - Hamiid Rizky Ardianov; Kukuh Lukiyanto; Irmawan Rahyadi (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This study employs a systematic literature review (SLR) approach, using the PRISMA protocol, to analyze 37 articles on tribal entrepreneurship in Indonesia. The findings highlight the dual role of entrepreneurship in preserving cultural heritage and fostering economic empowerment, while also addressing challenges such as limited resources and barriers to digitalization. These insights underscore the importance of integrating cultural values in entrepreneurial practices while modernizing with innovative technologies to enhance business sustainability and community engagement.